CHROMIUM REMOVAL FROM POLLUTED WATER AND ITS INFLUENCE ON BIOCHEMICAL AND PHYSIOLOGICAL PARAMETERS IN ALGAL CELLS USED FOR PHYTOREMEDIATION - PLUGARU, Sebastian Radu Cristian; RUSU, Tudor; MOLNAR, Katalin; FODORPATAKI, Laszlo (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The aim of the study is to evaluate the suitability of a local strain of the microalga Scenedesmus opoliensis in remediation of water pollution with different amounts of chromium(VI), and also to identify new biochemical and physiological markers for a more reliable indication of sustainability and efficiency of bioextraction and phytoaccumulation processes. Quantitative analysis of photosynthetic pigments reveals that the chlorophylls to carotenoids ratio is a sensitive marker of chromium toxicity and of algal metal tolerance on which the remediative capacity relies. From among the chlorophyll fluorescence parameters, the Fv/Fm ratio, related to potential quantum yield of photochemical reactions, indicates that alkaline pH of the medium (8.65-9.15) favors algal vitality as compared to acidic conditions with pH values around 5. The highest extraction rate (91%) is achieved upon exposure of algae for one week to lower chromium concentrations (5 µM) in alkaline water environment, and a longer exposure time does not increase bioaccumulation. These results may directly contribute to optimization of remediation technology for chromium-polluted water, providing new markers and a new algal strain to be introduced in wastewater treatment.